Pengaruh Komunikasi Terapeutik Perawat terhadap Tingkat Kecemasan pada Pasien Pre Operasi - Sulastri, Sulastri; Trilianto, Arif Eko; Ermaneti, Yunely (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2019)
Anxiety is a problem associated with all sorts of foreign procedures that occur when a person feels threatened physical or psychological. Hospitalization and a series of actions procedures before surgery can also cause acute distress and increased anxiety in patients. Range of possible bad could happen that would endanger patients, patients with anxiety showed symtomp irritability, insomnia, restless, listless, crying and not sleeping soundly. The design used is Pre Experiment. Amount of samples 28 respondents. Intake of sampel by using is technics of Quota Sampling. Data collecting use Questionnaire. Processing data using T test (T-Test). From the analysis of data obtained 7.111 T and T table calculated with α = 0.05 is 2.052, 7.111 calculated in order to obtain T> T table 2.052, then the H1 accepted which means there's Influence Of Communications of Terapeutik Nurse To Storey Level Dread Of Patient of Pre Operate surgical operation room RSUD dr. Abdoer Rahem sub-province of Situbondo. This is seen in patients of pre operation anxiety levels are affected by therapeutic communication. So that each respondent is expected to more actively ask anything that is not known to the officer about the anxiety that occurs. Keywords : Therapeutic Communication, Dread, Pre Operation